(untitled) (Bulletin of the Institute of Chemistry and Chemical Technology, 2022)
According to the hydrogeological zoning in the western region of Mongolia, there are 9 hot springs such as Gantz mod, Chikhertei, Aksu, and Indert hot spring of Mongol-Altai mountains, and Otgontenger, Khojuul, Zart, Tsetsuuh, and Ulaan Khaalga of Khangai mountains. In this study, we selected these hot springs as research objects. The aim was to determine the chemical composition and chemical composition of the mineral rocks dissolved in the springs, determine the water-rock interaction, determine the temperature of the underground hot water in the springs, and determine the depth of circulation of the underground reservoir. The hot springs of Mongolia-Altai region have a temperature of 23.3-33°C or warm, pH 8.3-9.19 alkaline environment and chemical composition is Aksu, Gantzmodi spring HCO3-Na, Chikhertei spring HCO3-SO4-Na, Indert hot spring SO4-Na. It was determined that the springs of Khangai region have a temperature of 33-45.5°C, pH 8.36-9.56 alkaline environment, Zart, Tsetsuuh, and Ulaan Khaalga springs belong to the SO4-Na type, and Khojuul and Otgontenger springs belong to the HCO3-SO4-Na type. It was found that the chemical composition of the hot springs of Mongolia-Altai region depends on the altitude, and the mineralization increases from northwest to southeast, from HCO3-Na to HCO3-SO4-Na, and to SO4-Na in the lowlands. The temperature of the underground reservoir of hot springs in the western region was determined to be 98-134°C by chemical geothermometry. When calculating the depth of the underground reservoir of these hot springs, it was proved that they are 2600- 3300 meters below the surface in Mongolia-Altai region, and 1500-1600 meters in Khangai region. Underground hot water in western region of Mongolia can be developed for direct use, such as thermal energy, greenhouse farming, fish breeding, snowmelt, bathing, swimming pools, water sports, spas, and nature tourism. Furthermore, it was also determined that the temperature of underground hot water is 98-134°C, so it is possible to extract electricity by using the binary system. Монгол орны Баруун бүсийн халуун рашааны гидрогеохимийн судалгаа Хураангуй: Монгол орны Баруун бүсэд гидрогеологийн бүсчлэлээр авч үзвэл Монгол-Алтайн мужийн Ганц мод, Чихэртэй, Аксу, Индэртийн халуун рашаан, Хангайн мужийн Отгонтэнгэр, Хожуул, Зарт, Цэцүүх, Улаан хаалга зэрэг 9 халуун рашаан тархсан байдаг. Эдгээр халуун рашааныг судалгааны обьект болгон сонгон авч рашааны химийн найрлага, рашаанд ууссан эрдэс чулуулгийн химийн найрлагыг тодорхойлж, ус-чулуулгийн харилцан үйлчлэлийг тогтоож, рашаануудын газрын гүний халуун усны температурыг тодорхойлж, газрын доорх усан сангийн эргэлтийн гүнийг тогтоохыг зорьсон юм. Монгол-Алтайн мужийн халуун рашаанууд нь температурын хувьд 23.3-33°С буюу бүлээн, рН 8.3-9.19 шүлтлэг орчинтой, химийн найрлагын хувьд Аксу, Ганц модны рашаан HCO3-Na, Чихэртэй рашаан HCO3-SO4-Na, Индэртийн халуун рашаан SO4-Na төрөлд хамаарагдаж байна. Хангайн мужийн рашаанууд нь 33-45.5°C температуртай, рН 8.36-9.56 шүлтлэг орчинтой, Зарт, Цэцүүх, Улаан хаалганы рашаанууд SO4-Na төрөл, Хожуул, Отгонтэнгэрийн рашаанууд HCO3-SO4-Na төрөлд тус тус хамаарагдаж байгааг тодорхойлов. Монгол-Алтайн мужийн халуун рашаануудын химийн найрлага өндөршлөөс хамаараад баруун хойноосоо зүүн урагшаа чиглэлд эрдэсжилт нь нэмэгдэж HCO3-Na найрлагаас HCO3-SO4-Na болж, нам доор газраа SO4-Na төрөл болж өөрчлөгдөж байгааг тогтоолоо. Баруун бүсийн халуун рашааны газрын гүний усан сангийн температурыг химийн геотермометрийн аргаар тооцоход 98-134°С байгааг тогтоолоо. Эдгээр халуун рашаануудын газрын доорх усан сангийн гүнийг тооцоолоход, Монгол-Алтайн мужийнх газрын гадаргаас доош 2600-3300 метрт, Хангайн мужийнх 1500-1600 метрийн гүнд оршиж байгааг тогтоосон. Баруун бүсийн газрын гүний халуун усыг ашиглан шууд хэрэглээнд буюу дулааны эрчим хүч, хүлэмжийн аж ахуй, загас үржүүлэх, цас хайлуулах, усанд орох, бассейн, усан спорт, рашаан сувилал, байгалийн аялал жуулчлал зэргээр хөгжүүлэх боломжтой. Мөн газрын гүний халуун усны температур нь 98-134°С байгаа тул бинарын системийг ашиглан цахилгаан эрчим хүч гарган авах боломжтойг тогтоолоо. Түлхүүр үг: геотермал ус, геотермометр, эрчим хүч